Removing the division into categories between cycling and para-cycling (Handbike category H) by designing a single performance and training activity - Russo, A.; Invernizzi, P. L.; Scurati, R.; Ceruso, R.; Altavilla, G. (Journal of Human Sport & Exercise, 2021)
Cycling and all categories of para-cycling including Handbike are cyclical sports, that is, sports characterized using a specific skill, continuous skill. To separate competitions between cyclists and paracyclists, there is a classification system. The study in aims to design one activity performance and training, to eliminate the division into categories between cycling and para-cycling (Handbike), since this does not favour the integration and sporting inclusion of the two groups of athletes. The differences in performance will be identified between: cyclists and paracyclists with spinal cord injury or amputation of the lower limbs (H). Then will proceed to design and verify an activity capable of making the two categories compete and train together, eliminating the differences in performance through the use of a "counterweight" and using a mixed training, HIIT (High Intensity Interval Training) and Endurance. The sample taken into consideration is composed of 5 cyclists and 5 paracyclists (H) aged between 19 and 38 years. To achieve the goal, the study was based on the method of analysing the scientific literature, detecting the various parameters in the race and using mathematical statistical methods, such as Multiple Regression and the T-Test for independent samples. The analysis of the results of this study shows that; between cyclists and para-cyclists who participated, there are substantial differences in performance, thanks to the data obtained from multiple regression, in which we find an R-squared value that is .999975008, also the only positive coefficient among the independent variables is that of power (6.760634791). This means that of all the reported values, it is the only one that directly affects performance.